MURABAHAH BUYING AND SELLING PERSPECTIVE IN ISLAMIC ECONOMY: PERSPEKTIF JUAL BELI MURABAHAH DALAM EKONOMI ISLAM - Asriani, Elza (UPMI Proceeding Series, 2023)
A good sale and purchase is one in which there is honesty, truthfulness, and not disobeying Allah. To achieve such a sale and purchase, there are elements that must be met, namely in the form of terms and the pillars of the sale and purchase itself. Murabahah financing. Murabaha is a sale and purchase contract between two parties parties, where the buyer and seller agree on a selling price, which consists of: the purchase price plus the cost of purchase and profit for the seller. Another understanding of murabaha is a contract of buying and selling goods with stated the acquisition price and profit (margin) agreed by seller and buyer. Murabaha can be done in cash or in kind pay deferred or pay in installments. Another understanding murabaha is a sale and purchase transaction, where the bank gets a number of profitS. In this case, the bank becomes the seller and the customer becomes the buyer The terms of the goods being traded are goods that are lawful, provide benefits, full property rights of the seller and goods according to the specifications desired by the buyer. The terms of the contract must be clear both the specifications of the goods and the price and do not contain clauses that depend on the legality of the transaction. Murabahah law according to the scholars is permissible as long as there is no binding obligation to complete the transaction, both written and verbal before getting the goods into possession and delivery